Density and Viscosity Matched Newtonian and non-Newtonian Blood-Analog Solutions with PDMS Refractive Index - Brindise, Melissa C. (Exp Fluids, 2018)
Optical imaging is commonly used to investigate biological flows and cardiovascular disease using compliant silicone polydimethysiloxane (PDMS) Sylgard 184 geometries. However, selecting the working fluid with blood density and viscosity, and PDMS index of refraction (RI) for such experiments is challenging. Currently, water-glycerol is commonly used and sodium iodide (NaI) often added to increase the index of refraction without changing fluid viscosity. But the resulting fluid density is well above blood. Moreover, NaI is expensive, has safety and material discoloration concerns, and has been reported to affect non-Newtonian fluid behavior. Here, we present a new blood analog alternative based on urea. Urea is approximately five to fifteen times less expensive than NaI, safe and easy to handle, optically clear, and causes no discoloration. Water-glycerol-urea solutions, unlike those with NaI, simultaneously matched the density and viscosity of blood and RI of PDMS. Water-xylitol and water-xylitol-urea solutions are also possible blood analog solutions. Xanthan gum (XG)-water-glycerol non-Newtonian solutions maintained similar viscoelastic properties throughout the range of weight percent (about 15–25%) of urea and NaI used here. The results showed that the XG weight percent affected viscoelastic properties more than the weight percent of urea or NaI tested in this study. Overall, we demonstrate urea is useful for PDMS blood analog experiments and should also be considered as an inexpensive additive, and an alternative to NaI.